Shenling Baizhu Powder Alleviates TNBS-Induced Colitis in Rats by Improving Intestinal Epithelial Permeability and Inhibiting Inflammation Through the TLR5/MyD88/NF-κB Pathway - Rao, Kehan; Qin, Shumin; Yang, Yuanming; Zhan, Kai; Wu, Haomeng; Zheng, Huan; Huang, Shaogang (Frontiers in Pharmacology, 2022)
Aim of the study: To evaluate the protective effect and mechanism of Shenling Baizhu Powder (SBP) on TNBS-induced colitis. Methods: Rats were given TNBS to establish the model of colitis and subsequently treated with different doses of SBP or mesalazine. In addition, the expression of TLR5/ MyD88 / NF-κB signaling pathway and critical targets of the intestinal mucosal barrier was detected by immunochemical analysis techniques. Results: SBP significantly ameliorated the symptoms of TNBS-induced colitis in rats and reduced the secretion of pro-inflammatory cytokines. SBP can effectively strengthen epithelial barrier integrity in TNBS-induced colitis by increasing the secretion of mucin and tight junction and inhibiting apoptosis. Furthermore, we identified the crucial role of the TLR5/ MyD88 / NF-κB signaling pathway in exerting the therapeutic effect of SBP. Conclusion: The results of our study suggest that SBP has therapeutic effects on TNBS-induced colitis and potential value in treating and maintaining remission of colotis.